PENINGKATAN KOMPETENSI PEDAGOGIK GURU-GURU IPA SMP SOLOK SELATAN MELALUI PENDAMPINGAN IMPLEMENTASI PEMBELAJARAN KONTEKSTUAL BERDASARKAN PENDEKATAN SAINTIFIK - Hufri Hufri (Fakultas MIPA Universitas Negeri Padang, 2018)
Less optimal learning at the junior high school level, especially in science subjects, in South Solok District, especially in natural science subjects can be seen from the results of the 2016 UN ranking which is ranked 16 of the 19 cities / districts in West Sumatra. This happens, because the competence of teachers in designing and implementing contextual learning based on the scientific approach is still low. This community partnership program aims to improve pedagogic competence of science teachers in South Solok District Junior High School through mentoring in designing contextual learning based on the scientific approach and implementing it in the classroom. The method used consists of orientation and discussion stages, implementation preparation stages, implementation stages by providing assistance in designing contextual learning with a scientific approach (such as preparing RPP, Multimedia, and guidance for teachers) and assisting teachers in implementing contextual learning with a scientific approach , the monitoring and evaluation phase and the last stage of data analysis and report preparation. Data collection instruments used are questionnaire sheets to assess the implementation of activities and padegogic ability tests. The data analysis used was paired t test. Based on data analysis results of pretest and posttest, obtained an increase in the average value from 14.17 to 20.35, with an interval of values ​​from 0 to 30. So the average value, posttest is higher than the pretest value. From the t test also obtained a significance result of 0.000 <0.05, so it can be concluded that there are significant differences between the results of the pretest and posttest. Furthermore, based on the questionnaire given at the end of the training activity, the results showed that the participants stated that this activity was very useful and related to the subjects taught at school.